Save the World on Your Own Time. - Fish, Stanley Eugene (Oxford University Press, 2012)
""[Save the World on Your Own Time] is invariably smart, stimulating, and provocative. It is filled with insights and crackles with verve. It is a joy to take in.""--Texas Law Review